Root cause analysis of epidural spinal cord stimulator implant infections with resolution after implementation of an improved protocol for surgical placement. Issue 4 (July 2019) - Arnold, Forest W; Bishop, Sarah; Johnson, David; Scott, LaShawn; Heishman, Crystal; Oppy, Leah; Ball, Tyler; Sharma, Mayur; Angeli, Claudia; Ferreira, Christie; Chen, Yangsheng; Harkema, Susan; et al.
Background: Placing a spinal stimulator for the purpose of restoring paralysed function is a novel procedure; however, paralysis predisposes people to infection. Preventing surgical site infections is critical to benefit this population. Objective: The objective of this study was to review the root cause analysis of postoperative wound infections by a hospital epidemiology team following implantation of epidural spinal cord neurostimulators in patients with chronic spinal cord injury. Methods: A team was assembled to review the case of every individual who had been enrolled to receive a neurostimulator at the facility. A root cause analysis was performed evaluating five categories: the patient; equipment; facility/environment; procedure; and personnel. Findings: The root cause analysis included 11 patients. Two patients became infected. Three others dehisced their wound without becoming infected. All patients were given preoperative antibiotics on time. A mean of 17 personnel were in the operating room during surgery. Vancomycin powder was used in the patients who either dehisced their wound or became infected. Conclusions: The root cause analysis provides guidance for other institutions performing the same novel procedure. This analysis did not reveal a direct association, but did generate several areas for improvement including increasing pre-surgical screening, cleaning transient equipment (e.g., computer screens), limiting traffic in the operating room, using new sterile instruments for each stage of the procedure, not reopening the back incision, not applying vancomycin powder, and using an antimicrobial envelope for the stimulator.